The role of apoptosis in pathogenesis of type 1 diabetes mellitus - Elena Vladimirovna Pekareva; Tatiana Vasil'evna Nikonova; Olga Mikhailovna Smirnova (Сахарный диабет, 2010)
Type 1 diabetes mellitus (DM1) is known to be associated with progressive destruction of pancreatic beta-cells. Apoptosis plays the key role in this destructiveprocess. The paper focuses on major mechanisms underlying activation of beta-cell apoptosis and its role in regulation of immune processes inpatients with DM1.